Designing a Causal Model of Relationships Between Emotional Branding Components in the Apparel Industry with a Fashion Textile Approach - Ahmadzadeh Ardabili, Behnaz; Hosseini , Seyed Hossein; Rostami, Mohammad Reza; Sanei, Mehdi (Business, Marketing, and Finance Open, 2026)
The aim of this study is to design a causal model of the relationships between emotional branding components in the Iranian apparel industry with a fashion textile approach. The research methodology was based on a mixed-methods design. In the qualitative phase, thematic analysis was employed (King & Horrocks, 2010) to extract components and indicators. The qualitative research population consisted of apparel branding experts (managers, marketing specialists, professors, and researchers), and through purposive and snowball sampling, semi-structured interviews were conducted with 15 individuals until theoretical saturation was achieved. The qualitative findings were analyzed using MaxQDA software, and the final components were validated through the fuzzy Delphi technique. In two screening rounds, expert consensus was obtained. In the quantitative phase, the statistical population consisted of consumers of fashion apparel products, and a sample of 384 individuals was selected through stratified random sampling using Cochran’s formula. Quantitative data were collected through a researcher-made questionnaire, with validity confirmed by confirmatory factor analysis and reliability established using Cronbach’s alpha and composite reliability. For causal modeling, partial least squares structural equation modeling (PLS-SEM) was applied using SmartPLS software, while causal network analysis was conducted with the fuzzy DEMATEL technique. The results showed that themes such as design and aesthetics, brand elements, sensory-physical factors, and social responsibility play key and driving roles in shaping emotional branding and consumer experience. Moreover, network analysis indicated the causal precedence of design and brand factors, as well as consequences such as consumer experience and socio-cultural dimensions. By presenting a localized and multilayered model, this study addresses the gap in previous research regarding a comprehensive and causal explanation of emotional components in the apparel industry of Iran and provides a valid analytical tool for policymakers and industry managers.